1991
DOI: 10.1007/bf02536432
|View full text |Cite
|
Sign up to set email alerts
|

Sterols ofKalanchoe pinnata: First report of the isolation of both C‐24 epimers of 24‐alkyl‐Δ25‐sterols from a higher plant

Abstract: Eighteen sterols were isolated from the aerial parts ofKalanchoe pinnata (Crassulaceae) including four novel sterols,viz. (24R)‐stigmasta‐5,25‐dien‐3β‐ol (24‐epiclerosterol), (24R)‐5α‐stigmasta‐7,25‐dien‐3β‐ol, 5α‐stigmast‐24‐en‐3β‐ol, and 25‐methyl‐5α‐ergost‐24(28)‐en‐3β‐ol. 24‐Epiclerosterol and its Δ7‐analog occur together with their 24S/β‐epimers in the same plant making this the first report of the isolation of both C‐24 epimers of Δ25‐unsaturated 24‐alkylsterols from a non‐marine organism. Iodine‐catalyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…brasiliensis are mainly glycosylated flavonoids derived from aglycone patuletin [9], while for K . pinnata the constituents described are mainly steroids, bufadienolids, and glycosylated flavonoid derivatives of quercetin, kaempferol and luteolin aglycones [12, 16, 17, 18]. The main pharmacological studies of K .…”
Section: Introductionmentioning
confidence: 99%
“…brasiliensis are mainly glycosylated flavonoids derived from aglycone patuletin [9], while for K . pinnata the constituents described are mainly steroids, bufadienolids, and glycosylated flavonoid derivatives of quercetin, kaempferol and luteolin aglycones [12, 16, 17, 18]. The main pharmacological studies of K .…”
Section: Introductionmentioning
confidence: 99%
“…All the isolated compounds were identified by comparison of their MS and NMR spectra compared with data from the literature (McLean et al, 1987;Akihisa et al, 1991;Pouchert and Behnke, 1993;Faizi et al, 2001). Copies of the original spectra are obtainable from the author for correspondence.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Bufadienolides, bryophyllin-A, -B, -C and bersaldegenin-1, 3, 5-orthoacetate were isolated from the plant of Taiwan origin and was shown to possess hepato-protective activity and cytotoxicity [31,39-41,31]. Apart from this bryophyllol, bryophollone, bryophollenone, bryophynol, 2(9-decenyl) phenenthrene (I), 2(undecenyl) phenenthrene (II), 18α-oleanane, ψ-taraxasterol, α-and β-amyrins and their acetates, 24-epiclerosterol [24(R) stigmasta-5, 25-dien-3β-ol], 24(R) 5α-stigmasta-7, 25-dien-3β-ol, 5α-stigmast-24-en-3β-ol and 25-methyl-5α-ergost-24(28)-en-3β-ol were isolated from the plant leaves and other aerial parts [42,43]. Therefore, it is difficult to conclude from the present study that anti-HPV/anticancer activity observed in crude leaf extract or fraction F4 is displayed specifically by any single chemical entity.…”
Section: Discussionmentioning
confidence: 99%